Women and the Digitalization Strategies of Micro, Small, and Medium Enterprises in the New Normal Era - Junia Laksmanawati; Ahyar Yuniawan (Master of Management, School of Business and Management, Petra Christian University, 2021)
This paper is based upon research to study the development of women entrepreneurs in Indonesia with emphasis on motivation to begin small business (MSMEs) and digitalization strategies in doing their businesses. The research was based on a literature review and a small field survey of women holding small business (MSMEs) in Semarang. After analyzing the data from the interviews, many respondents stated that their early motivation in running their own businesses was as a means to get additional incomes in finance. Evidence shows that as entrepreneurs, dealing with digitalization is a thing that cannot be avoided in the new normal era. To optimize their business operations and revenue, some adjustments and strategies are conducted such as optimizing digital marketing, seeing business opportunities, creating innovations, creating new markets, and executing marketing plan.